A private equity structure to facilitate the effective post-commencement financing of business rescue - Reineck, Juan-Pierre (Department of Commercial Law, 2015)
Business rescue is a process through which a financially distressed company can be rehabilitated by providing for the temporary supervision of the company, the management of its affairs, business and property. Focused research indicates that one of the main reasons that business rescues in South Africa have failed is due to the lack of post-commencement rescue finance. This dissertation puts forward a researched and suggested financial structure solution that combines two comparatively new concepts in South African corporate law, being business rescue from the Companies Act 71 of 2008 and the financing of venture capital companies in the Income Tax Act 58 of 1962. The outcome of the suggested post-commencement finance structure is that the investors investing in this structured solution would receive an immediate benefit in the form of a tax deduction and a reduction in the financial risk exposure of the investment. In turn, the company in business rescue receiving the investment funds from this finance structure would also benefit from fewer cost burdens associated with traditional debt financing (i.e. servicing of the debt) and thereby increase the probability of a successful business rescue, concomitantly resulting in the improvement in economic activity and importantly, the retention of jobs in South Africa that it so desperately needs.